PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA BAGI PELAKU UMKM DI DESA JIMBARAN KABUPATEN BADUNG - Putu Ratna Windusara Putri; Fahmi Tanjung; I Made Wisnu Wardana; I Made Sujana (Yayasan Nusantara Hasana Berdikari, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting economic growth, employment creation, and community welfare. However, many MSME actors still face challenges in financial management, particularly in preparing simple financial statements. Limited accounting knowledge often leads to poor financial recording practices, making it difficult for business owners to assess business performance and access financing opportunities. This community service program aimed to improve the financial literacy and accounting skills of MSME actors in Jimbaran Village through training and mentoring in preparing simple financial statements. The methods employed included socialization, training sessions, practical exercises, mentoring, and evaluation. A total of 40 MSME actors participated in the program. The results showed significant improvements in participants’ understanding of financial recording, preparation of income statements, cash flow records, and simple balance sheets. Participants were also able to implement financial recording practices in their daily business activities. This program contributed positively to strengthening MSME financial governance and enhancing business sustainability.